Josephson currents in c-axis and ab-plane orientated MgB2/normal-metal/MgB2tunnel junction - Bumned Soodchomshom (2018)
The critical Josephson currents in a S1/N/S2double interfaces tunnel junction are calculated by using the linearized Usadel equation to derive the anomalous Green's function in the normal-metal layer (N). Both of the S1and S2layers are formed by MgB2but due to the proximity effect have different characteristics. Two orientations of the MgB2superconductors are considered. In one junction, the c-axis of MgB2in the S-layer is perpendicular to the interface, while in the other, the ab-plane is perpendicular to the interface. The different transparencies of the two MgB2/normal-metal interfaces, the normal state resistances of the currents flow from S1to S2in each band and the N-layer thickness are taken into account. The critical Josephson currents in both the c-axis and ab-plane oriented junctions are studied near the critical temperature. The predicted currents are compared with the experimental currents and are seen to fit the data above 0.4TC. © 2007 Elsevier B.V. All rights reserved.